The Impact of Movies on Tourism among Egyptian Youth - Abou Zeid, Dina Farouk (Mediterranean Journal of Social Sciences, 2021)
The research study aims to examine the impact of movies on tourism among Egyptian youth by studying the different genres of movies and the different types and forms of tourism besides applying infotainment to discover the elements of information and entertainment in movies which encourage the youth to travel. A survey is conducted of a disproportionate stratified sample of 500 Egyptian university students divided equally between private and public universities and between males and females who have passion for traveling, travel at least once a year and are members of travel Facebook groups. The results show that Egyptian and non-Egyptian movies encourage Egyptian university students to travel abroad. The most popular types of movie-induced tourism among the youth are traveling to destinations portrayed in movies, organized tour of portrayed locations, tour of studio sets and movie-themed park. The findings indicate that movie- induced tourism is affected by movies' infotainment. Received: 22 July 2021 / Accepted: 28 September 2021 / Published: 5 September 2021